Kolaborasi Interpol dalam Mengatasi Tindak Pidana Ekonomi Lintas Negara: Pendekatan Hukum Pidana Internasional dan Regional - Warni Rifani Aisya; liza Marina; Ani Purwati (PT. Hasba Edukasi Mandiri, 2025)
Transnational economic crimes, such as money laundering, transnational corruption, and international financial fraud, have evolved with globalization and technological advancements. The complexity of these crimes requires strong international cooperation to effectively address them. Interpol, as an international police organization, plays a crucial role in facilitating collaboration between countries through information exchange, the issuance of red notices, and the coordination of cross-border operations. This study aims to analyze Interpol's role in addressing transnational economic crimes and review the international and regional criminal law approaches that underpin this collaboration. Through a literature review and a normative juridical approach, it is found that the effectiveness of collaboration depends on the harmonization of international legal instruments such as UNCAC and UNTOC, as well as the support of regional frameworks such as ASEANAPOL and EUROPOL. However, challenges remain, including differences in legal systems, confidentiality, and the potential for protection by Interpol mechanisms. Therefore, strengthening institutional capacity, trust between countries, and regulatory reform are needed to encourage more effective and equitable collaboration.